Analisis Biaya Iklan Dan Biaya Live Streaming Pada Pendapatan Elemate Shop - Roisah Putri, Aulia; Hendri, Nedi; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
The purpose of using marketing through advertising and live streaming is to introduce products to the public so that sales occur and generate income in accordance with business targets. The use of marketing through advertising and live streaming certainly requires costs. Thus, this study aims to analyze advertising costs and live streaming costs on Elemate Shop's revenue. The method used in this study is a qualitative descriptive method. The data used in this study is secondary data, with the data used in the form of Elemate Shop's monthly financial reports for February-June 2023. The results of this study indicate that advertising costs, live streaming costs, and revenue for 5 months have increased. The increase in advertising costs and live streaming costs affects the increase in Elemate Shop's revenue